2016
DOI: 10.1364/ao.55.008266
|View full text |Cite
|
Sign up to set email alerts
|

All-optical detection of acoustic pressure waves with applications in photoacoustic spectroscopy

Abstract: An all-optical detection method for the detection of acoustic pressure waves is demonstrated. The detection system is based on a stripped (bare) single-mode fiber. The fiber vibrates as a standard cantilever and the optical output from the fiber is imaged to a displacement-sensitive optical detector. The absence of a conventional microphone makes the demonstrated system less susceptible to the effects that a hazardous environment might have on the sensor. The sensor is also useful for measurements in high temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Erbium‐doped ring lasers, [ 139 ] DFB, [ 140,141 ] normalCO2${\rm{C}}{{\rm{O}}_2}$ lasers, [ 142 ] visible LEDs, [ 143 ] IR LEDs, [ 144 ] and THz diodes [ 145,146 ] are among the sources used with PA cells equipped with cantilevers. Lasers are more common than LEDs due to their higher optical power.…”
Section: Tunable Diode Laser Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Erbium‐doped ring lasers, [ 139 ] DFB, [ 140,141 ] normalCO2${\rm{C}}{{\rm{O}}_2}$ lasers, [ 142 ] visible LEDs, [ 143 ] IR LEDs, [ 144 ] and THz diodes [ 145,146 ] are among the sources used with PA cells equipped with cantilevers. Lasers are more common than LEDs due to their higher optical power.…”
Section: Tunable Diode Laser Systemmentioning
confidence: 99%
“…The detection of the PA signal was conducted using a bare single mode fiber SM acting as a cantilever. The output light from the fiber was imaged on a displacement detector [ 143 ] as shown in Figure a. It is easy to control the fiber's resonance frequency by adjusting its length before use since the resonance frequency is inversely proportional to the square of the fiber length.…”
Section: Tunable Diode Laser Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Westergaard et al reported a CEPAS based on a stripped single-mode fiber [63] . The fiber itself was used as a cantilever and the emergent light of the fiber was detected by a split detector.…”
Section: Cepas Based On Different Displacement Detection Techniquesmentioning
confidence: 99%
“…Of the many optical spectroscopic methods developed during the past century, photoacoustic spectroscopy (PAS) [ 17 , 18 , 19 , 20 , 21 ] has attracted considerable interest due to its powerful, yet simple, trace gas detection method and capability to detect multiple gasses with a single device. The PAS method is different from other optical absorption-based methods, where the absorbed energy translates into kinetic energy, which forms an acoustic wave that can be detected with a simple pressure transducer [ 17 , 22 , 23 ]. A variant of PAS is quartz-enhanced photoacoustic spectroscopy (QEPAS), which was introduced in 2002 [ 23 ] and is today an established spectroscopic technique [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%